Cold shock induces apoptosis of dorsal root ganglion neurons plated on infrared windows. Issue 12 (21st June 2015) - Aboualizadeh, Ebrahim; Mattson, Eric C.; O'Hara, Crystal L.; Smith, Amanda K.; Stucky, Cheryl L.; Hirschmugl, Carol J.
<x xml:space="preserve">Abstract</x> The effect of sample preparation and substrate choice in the apoptosis of dorsal root ganglion neurons using FTIR widefield microscopy.